Evaluasi Biaya dan Waktu Pelaksanaan Pekerjaan Fondasi Bore Pile Proyek Rumah Susun BPK RI Kota Gorontalo - Abdul Gandi; Mohamad Yusuf Tuloli; Arfan Usman Sumaga (Transbahasa, 2024)
Bore pile foundations are a type of deep foundation that does not displace surrounding soil, commonly used alongside pile foundations. Key elements in construction projects are cost, time, and quality, making the evaluation of cost and time crucial to meet project plans without sacrificing quality. This study focuses on: (1) calculating bore pile productivity, (2) determining the volume of completed work, (3) assessing the unit price of bore pile foundations, (4) comparing the unit price using the AHSP Cipta Karya Permen PUPR No. 28 of 2016 with field conditions, (5) identifying delays in bore pile work, and (6) comparing project timelines using the S curve. The analysis shows that the total cost based on AHSP is Rp. 3,676,848,177.59, while the field cost is Rp. 4,266,992,505.98. The AHSP schedule estimated 77 days, but the field completion was 84 days, indicating a 7-day delay. Factors contributing to these discrepancies include differences in pricing, project and material delays, equipment issues, and weather conditions.